General determinants of aging: The size and geometry of living beings - Jorge Barragán; Sebastián Sánchez (Archive of Gerontology and Geriatrics Research - Peertechz Publications, 2023)
The relationship between basal metabolic rate and weight changes which are a normal part of the human aging process can be represented in holographic form. The purpose of the study is to verify the validity of said representation through the development of the objectives, which are to examine the relationship between the total amount of energy lost and the amount of energy lost per unit of body mass, as well as the relationship that exists between the total amount of energy lost and body mass. There are previous studies that relate the size of living beings with their metabolic rate. Our study provides the foundation for the holographic description of that relationship. The analysis of the data allowed us to generate a coherent description of our notion using the tools at our disposal. According to the results of the study, there is a correlation that can be considered statistically significant between the basal metabolic rate per dry kilogram of an organism and the total amount of energy it expends. Based on this observation, we can conclude that the biological system in question satisfies the conditions of the holographic principle.